Deskripsi Pola Asuh Orangtua Dan Kepercayaan Diri Anak di TK Atifah Bontomanai Desa Maccini Baji Kec. Batang Kab. Jeneponto - Noviandriani; Besse Marjani Alwi; Nur Khalisah Latuconsina (NANAEKE: Indonesian Journal on Early Childhood Education, 2022)
This study aims to describe 1) parenting styles in Atifah Bontomanai Kindergarten, Maccini Baji Village, Batang District, Jeneponto Regency, and 2) children’s self confident in Atifah Bontomanai Kindergarten, Maccini Baji Village, Batang District, Jeneponto Regency. This research is quantitative descriptive. The subject in this study were respondents from the parent of students at Atifah Bontomanai Kindergarten,Maccini Baji Village, with a total sample of 16 people selected through purposive sampling. Data collection was carried ot using questionnaire to measure parenting styles and children’s self confidence. The data obtained were analyzed usin descriptive statistic. The result showed: 1) the types of parenting used by parents today in increasing their children’s self confidence are authoritarian parenting with an average of 40%, permissive parenting with an average of 13%, and democratic parenting with an average of 47%,2) on the child’s self confidence variable, and independent self confidence indicator of 25%, not experiencing frustration by 12%, not depending on others by 19%, children being able to accept new challenges by 12%, children have emotions that alive but still stable by 13%, children find it easier to communicate and help others by 19%. The implication of this research is that parents should provide the right parenting style for children so that children's self-confidence can develop properly.